Evaluation of cyanobacteria biomass derived from upgrade of phycocyanin fluorescence estimation - Tinkara Rozina; Bojan Sedmak; Maja Zupančič Justin; Andrej Meglič (Acta Biologica Slovenica, 2017)
The number of harmful cyanobacterial blooms has increased significantly at the global level in recent years. One of the characteristics of cyanobacteria that gives them advantage over other phytoplankton organisms are auxiliary photosynthetic pigments, such as phycocyanin. This fluorescent pigment emits light at a different wavelength as chlorophyll and can therefore be used for detection of cyanobacteria in situ. In this study we used submersible phycocyanin fluorescence sensors and compare their voltage output to concentration of extracted phycocyanin, cell counts and biovolume. The relation was linear in all three cases; however, the variability of regression line slopes between different cyanobacteria strains was high in the case of PC extract concentration and cell count. The highest uniformity in the linear fits was between fluorescence signal and biovolume therefore making it the best candidate for fluorescence sensor voltage output conversion. In the context of this work we also compared different methods for PC extraction. Modifying the equations by subtracting the absorption at 750 nm almost entirely reduces the false PC concentration estimation due to sample turbidity.